Mapping the metabolic protein interactome that supports energy conservation at the limits of life - Williams, Seré Anne, author; Santangelo, Thomas, advisor; Hansen, Jeffrey C., committee member; Pilon, Marinus, committee member; Anderson, G. Brooke, committee member; Snow, Christopher, committee member (Colorado State University. Libraries, 2024)
Distinct metabolic strategies yield energetic gains from a wide variety of substrates, yet only three overarching methods of energy conservation have been defined: substrate level phosphorylation, the generation of a charged membrane, and electron bifurcation. The dominant theme of known energy conservation mechanisms suggests that energy is conserved through the selective movement and management of electrons, thus essentially all life relies on redox (reduction and oxidation) reactions. Small molecule redox cofactors (such as NAD(P)+) and proteinaceous electron carriers (such as ferredoxins) are employed as electron carriers throughout the biosphere. Proteinaceous electron carriers offer the potential for selective protein-protein interactions to bridge reductive flow from catabolic reactions to the membrane, providing a "proteinaceous electron highway" for efficient electron shuttling. Specific redox protein partnerships have been shown to adapt to changing physiological conditions, suggesting that proteinaceous electron flux is tunable and provides a level of selectivity not possible with small molecule electron transport. While electron flux through a tunable and regulated system of protein interactions can offer exceptional energy conservation strategies, large gaps remain in our knowledge of how electron flux is regulated in vivo. Identification of bona fide in vivo protein assemblies – and how such assemblies dictate the totality of electron flow and thus cellular metabolism – is an important milestone to understand the regulation imposed on metabolism, energy-production, and energy conservation. Resolving the dynamic nature of nanoscale interactions in living systems is arguably the current frontier of molecular biology, and combinatorial methods – which layer multiple in vitro and in vivo techniques with large data analysis – have come to the forefront. This dissertation addresses energy conservation strategies of in vivo protein associations in a model, genetically accessible, hyperthermophilic archaeon (Thermococcus kodakarensis) by mapping the metabolic protein interactome using affinity purification mass spectrometry (AP-MS) and generating engineered strains where fusion proteins selectively redirect electron flux in vivo. Twenty-five proteins involved in distinct metabolic functions were tagged to reveal that each tagged-protein interacts with ~ thirty proteins on average. These interactions connected disparate functions suggesting catabolic and anabolic activities may occur in concert -- in temporal and spatial proximity in vivo. The AP-MS method also refined our understanding of previously determined stable complexes suggesting that protein complexes in vivo likely adapt to redox conditions. Engineered strains linking a proteinaceous electron donor to a proposed electron acceptor were viable and impacted electron flux in vivo. Fusion strains linking a ferredoxin to the hydrogen-generating respiratory system increased hydrogen gas output ~8% on average with one strain showing a ~45% increase over wild type. Fusion strains impacting lipid saturation were shown to inhibit saturation, and future studies aim to determine if electrons can be redirected from the vast reductant sink of lipids to the generation of hydrogen gas, a valuable biofuel.
Keywords: biofuels; hyperthermophile; protein networks; fusion proteins; Archaea; metabolic interactome